Catecholaminergic neurons in the comissural region of the nucleus of the solitary tract modulate hyperosmolality-induced responses - Freiria-Oliveira, André H. [UNESP]; Blanch, Graziela T. [UNESP]; Pedrino, Gustavo R.; Cravo, Sergio L.; Murphy, David; Menani, José V. [UNESP]; Colombari, Débora S. A. [UNESP] (The American Physiological Society., 2015)
Noradrenergic A2 neurons of the nucleus of the solitary tract (NTS) have been suggested to contribute to body fluid homeostasis and cardiovascular regulation. In the present study, we investigated the effects of lesions of A2 neurons of the commissural NTS (cNTS) on the c-Fos expression in neurons of the hypothalamic paraventricular (PVN) and supraoptic (SON) nuclei, arterial pressure, water intake, and urinary excretion in rats with plasma hyperosmolality produced by intragastric 2 M NaCl (2 ml/rat). Male Holtzman rats (280-320 g) received an injection of anti-dopamine-β-hydroxylase-saporin (12.6 ng/60 nl; cNTS/A2-lesion, n = 28) or immunoglobulin G (IgG)-saporin (12.6 ng/60 nl; sham, n = 24) into the cNTS. The cNTS/A2 lesions increased the number of neurons expressing c-Fos in the magnocellular PVN in rats treated with hypertonic NaCl (90 ± 13, vs. sham: 47 ± 20; n = 4), without changing the number of neurons expressing c-Fos in the parvocellular PVN or in the SON. Contrary to sham rats, intragastric 2 M NaCl also increased arterial pressure in cNTS/A2-lesioned rats (16 ± 3, vs. sham: 2 ± 2 mmHg 60 min after the intragastric load; n = 9), an effect blocked by the pretreatment with the vasopressin antagonist Manning compound (0 ± 3 mmHg; n = 10). In addition, cNTS/A2 lesions enhanced hyperosmolality-induced water intake (10.5 ± 1.4, vs. sham: 7.7 ± 0.8 ml/60 min; n = 8-10), without changing renal responses to hyperosmolality. The results suggest that inhibitory mechanisms dependent on cNTS/A2 neurons reduce water intake and vasopressin-dependent pressor response to an acute increase in plasma osmolality.
Keywords: Blood pressure; C-fos expression; Osmoreceptor; Thirst; Vasopressin